Comparative study of ovariectomy and ovariohysterectomy in cats - Ummu Nasywah Qais An-Nadzilah; Raden Harry Soehartono; Riki Siswandi (Jurnal Medik Veteriner, 2026)
Ovariohysterectomy (OVH) is commonly used in the gonadectomy protocol of dogs and cats in Indonesia. Recent reports have shown that ovariectomy (OVE) is more preferred in the US and many European countries. Therefore, this study aimed to evaluate both OVE and OVH. A total of 26 cats were used, while OVH (11 cats) and OVE (15 cats) were conducted with standardized anesthetic and surgical protocols. Physical characteristics of cats, surgical variables, pain scores derived from behavior-based composite pain scales, surgical wound characteristics, and postoperative complications were analyzed. The results showed that skin and fascia incision lengths relative to the distance from the sternal manubrium to pubic rim were significantly greater in cats subjected to OVH (p < 0.05), compared to those of cats in OVE. However, the total surgical time was not significantly different for the two procedures. Significant differences were detected between the two groups during the evaluation period of pain scores in 24 hours (p < 0.001), with the best results recorded in OVE groups. The OVH groups showed more swelling and erythema than those in OVE (p < 0.001), and all wound complications resolved by 10 to 14 days postoperatively. A subsequent evaluation of postoperative serum progesterone concentrations, conducted after an eight-week period, showed that the mean concentrations remained consistent, suggesting the presence of extra-gonadal progesterone production. A follow up evaluation up to 16 weeks after the surgical intervention showed no substantial complications. In conclusion, OVE was not associated with any post-gonadectomy complications and could be a superior alternative to OVH.